Inter-annual growth response of three Miombo tree species to climatic effects. Issue 2 (2nd April 2020) - Munalula, Francis; Seifert, Thomas; Meincken, Martina
Abstract : Miombo woodlands cover a large part of Southern Africa and contribute an important wood source for the local wood industry. The already observed and further predicted changes in climatic patterns can be expected to affect the wood properties of Miombo tree species. The diameter growth response to climatic variables related to water availability and temperature of three Miombo woodland tree species ( Brachystegia spiciformis, Burkea africana and Isoberlinia angolensis ) was analysed using 245 trees samples in three climatic zones in Zambia. Sites were chosen to represent the range of site conditions under which these species grow in the Miombo woodlands of Zambia. The study sites differed in moisture availability and average temperature, as indicated by De Martonne's aridity index. Tree-ring width correlated with site conditions and differed significantly between sites. A positive correlation was found between mean annual precipitation and annual ring width, as well as growth variation, while growth was almost non-responsive to temperature variations. For all three species, trees growing on the outer limits of the species' range were found to be more responsive and sensitive to variability in annual rainfall than those growing under optimal conditions. All three species showed significant variation in inter-annual ring width with environmental conditions. Water availability was found to have a much larger effect than temperature, especially on drier sites.